A preparation method of lithium iron phosphate / nitrogen-doped carbon / nanocarbon composite material and the prepared material and use thereof
By coating the surface of lithium iron phosphate with nitrogen-doped carbon materials to form lithium iron phosphate/nitrogen-doped carbon/nanocarbon composite materials, the problems of insufficient conductivity of lithium iron phosphate and lithium ion diffusion rate are solved, and its rate performance and electrochemical lithium storage performance are significantly improved.
Patent Information
- Application Number
- CN202310834235.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-07-10
AI Technical Summary
As the cathode material of lithium-ion batteries, lithium iron phosphate has a low electronic conductivity and lithium ion diffusion rate, resulting in rapid capacity decay at high magnifications.
The preparation method of lithium iron phosphate/nitrogen doped carbon/nanocarbon composite material is adopted to form a multi-dimensional network structure carbonaceous material precursor by cryogenic freezing-thawing of biomass materials and nanocarbon materials under an alkali/urea aqueous system, and coated on the surface of lithium iron phosphate, and then calcined under an inert atmosphere to synthesize the composite material.
It significantly improves the conductivity and lithium ion diffusion rate of lithium iron phosphate, improves its rate performance, delays capacity attenuation, and broadens its commercial application in power batteries.
Smart Images

Figure CN116885168B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery positive electrode material preparation, and in particular to a preparation method of a lithium iron phosphate / nitrogen-doped carbon / nano-carbon composite material and the prepared material and application thereof. Background Art
[0002] At present, lithium-ion batteries have been widely used in 3C portable devices, electric vehicle power systems and energy storage systems due to their high energy density and long service life, and lithium iron phosphate is an important positive electrode material for lithium-ion batteries. The olivine structure of lithium iron phosphate gives it the advantages of structural stability, stable charge / discharge platform, high theoretical specific capacity, good thermal stability and chemical stability, and abundant raw material sources, environmental friendliness and high safety performance. However, the inherent crystal structure of lithium iron phosphate determines its low electronic conductivity and lithium ion diffusion rate, resulting in rapid capacity decay at high rates.
[0003] In view of the above-mentioned defects of lithium iron phosphate, people have improved the conductivity and ion diffusion rate of lithium iron phosphate by coating, doping modification and reducing particle size, thereby improving the rate performance of the material. Surface carbonaceous material coating is one of the effective methods to improve the conductivity of lithium iron phosphate materials. By dispersing or coating a small amount of conductive carbon between lithium iron phosphate material particles and on the surface of particles, it can effectively provide channels for electron transmission, enhance the conductivity between lithium iron phosphate particles, and reduce the polarization of the electrode, thereby improving the electrochemical performance of lithium iron phosphate materials. Based on existing research, how to further improve the performance of lithium iron phosphate as a positive electrode material for lithium-ion batteries has become a problem that people hope to solve. Summary of the invention
[0004] One of the purposes of the present invention is to provide a method for preparing a lithium iron phosphate / nitrogen-doped carbon / nanocarbon composite material. The composite material prepared by the method has higher electrical conductivity and lithium ion diffusion rate, and can be used as a positive electrode of a lithium ion battery to significantly improve its rate performance.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing a lithium iron phosphate / nitrogen-doped carbon / nanocarbon composite material comprises the following steps:
[0007] Step S1: dispersing biomass material powder in an aqueous solution of strong alkali and urea, adding a nanocarbon material solution, and obtaining a biomass / nanocarbon material mixed solution after a low-temperature freeze-thaw cycle, wherein the concentration of the strong alkali in the aqueous solution of strong alkali and urea is 0.2-3 mol / L, and the mass ratio of the strong alkali to urea is 1-4:1;
[0008] Step S2: adding lithium iron phosphate powder to the mixed solution, mixing to obtain a lithium iron phosphate / biomass / nano-carbon material mixed slurry, and then spray drying to obtain a lithium iron phosphate / biomass / nano-carbon composite material powder;
[0009] Step S3: placing the composite material powder into a muffle furnace, calcining at low temperature, washing and drying, to obtain a lithium iron phosphate / nitrogen-doped carbon / nano-carbon composite material precursor, wherein the low temperature calcination temperature is 200 to 380° C., and the calcination time is 1 to 12 hours;
[0010] Step S4: In an inert atmosphere, placing the precursor into a tube furnace, calcining in an inert gas atmosphere, with a sintering temperature of 600-1000° C. and a holding time of 1-10 h to obtain a lithium iron phosphate / nitrogen-doped carbon / nano-carbon composite material.
[0011] Preferably, the biomass material in step S1 is chitosan, cellulose or a mixture of the two in any proportion.
[0012] Preferably, the strong base described in step S1 is one of sodium hydroxide, potassium hydroxide or lithium hydroxide, or a mixture of two or more of them in any proportion.
[0013] Preferably, the nano-carbon material solution in step S1 is an acidified carbon nanotube or graphene oxide aqueous solution.
[0014] Preferably, the concentration of the nanocarbon material solution is 0.1-5 mg·mL -1 The mass ratio of the biomass material to the strong base is 1:4-12.
[0015] Preferably, in step S3, the spray drying parameters are set as follows: inlet temperature 150-260° C., outlet temperature 80-130° C., atomizer working pressure 100-250 kPa, and feed rate 60-200 mL / h.
[0016] Preferably, in step S4, the inert atmosphere is high-purity nitrogen or argon, and the heating rate is 2-10° C. / min.
[0017] Preferably, in step S2, the mass ratio of lithium iron phosphate to nano-carbon material is 60-120:1
[0018] The other two objects of the present invention are to provide a lithium iron phosphate / nitrogen-doped carbon / nano-carbon composite material prepared by the above method and the use of the composite material as a positive electrode material for lithium ion batteries.
[0019] The present invention has the following beneficial effects:
[0020] The present invention adopts a low-temperature freezing / dissolving method in an alkali / urea aqueous system to enable the biomass material and the nano-carbon material to interact with each other through electrostatics, hydrogen bonds, and hydrophilic-hydrophobic interactions, thereby forming an interwoven multi-dimensional network structure carbonaceous material precursor and coating it on the surface of lithium iron phosphate. Compared with traditional single carbon source coating, the coating effect of the multi-carbon source coated composite lithium iron phosphate positive electrode material is relatively more uniform and dense, thereby greatly improving the conductive properties of lithium iron phosphate and broadening the commercial application of lithium iron phosphate power batteries.
[0021] The present invention uses renewable natural biomass as a nitrogen source, and calcines it with lithium iron phosphate under inert gas to synthesize a biomass nitrogen-doped carbon-coated lithium iron phosphate composite material. The biomass raw material has a wide source, is low-cost and renewable, and is environmentally friendly and easy to obtain. The hydrophilicity of nitrogen atoms in the biomass material in the alkaline solution helps to improve its wettability and affinity to active materials, enhance the interaction with the positive electrode material, and reduce the activation energy of lithium ion diffusion; at the same time, it also helps to improve the affinity and wettability of the electrolyte, thereby improving the electronic conduction and lithium ion diffusion performance in lithium iron phosphate. Nitrogen atoms can provide carriers for the carbon material conduction band on the surface of lithium iron phosphate, improve the electronic conductivity of the material, and can also induce defects to reduce the activation energy of lithium ion diffusion, enhance the diffusion kinetics of lithium ions, improve the ionic conductivity and electronic conductivity of lithium iron phosphate, and then improve the rate performance of the material.
[0022] The invention has a simple process, is easy to prepare on a large scale, and has good application prospects and industrial potential. In addition, the preparation method provides a new way for high value-added utilization of biomass materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is an XRD spectrum of the lithium iron phosphate / nitrogen-doped carbon / graphene composite material prepared in Example 1 of the present invention;
[0024] Figure 2 is a SEM spectrum of the lithium iron phosphate / nitrogen-doped carbon / graphene composite material prepared in Example 1 of the present invention;
[0025] Figure 3 1 is a charge / discharge curve of a half-cell assembled with the lithium iron phosphate / nitrogen-doped carbon / graphene composite material prepared in Example 1 of the present invention at a rate of 1C;
[0026] Figure 4 1 is a charge / discharge curve of a half-cell assembled with the lithium iron phosphate / nitrogen-doped carbon / graphene composite material prepared in Example 1 of the present invention at a rate of 5C. DETAILED DESCRIPTION
[0027] The present invention will be further described below by means of specific embodiments:
[0028] Example 1 Preparation Example 1
[0029] Disperse 2 g of cellulose powder in 250 mL of a mixed aqueous solution with a sodium hydroxide / urea mass ratio of 2:1, where the sodium hydroxide concentration is 2 mol / L, containing 20 g of sodium hydroxide, 10 g of urea, and the mass ratio of cellulose powder to sodium hydroxide is 1:10. Add 80 mL of a 1 mg·mL -1 The graphene oxide solution was subjected to a low-temperature freezing-thawing cycle to obtain a uniform biomass / graphene oxide mixed solution, and the number of repeated low-temperature freezing / thawing was 3 times.
[0030] 8 g of lithium iron phosphate powder was added to the mixed solution and mixed thoroughly to obtain a lithium iron phosphate / biomass / graphene oxide mixed slurry; then spray drying was performed to obtain a lithium iron phosphate / biomass / graphene oxide composite material powder; the spray dryer operating parameters were set as follows: inlet temperature 180°C, outlet temperature 100°C, atomizer operating pressure 120 kPa, and feed rate 60 mL / h.
[0031] The powder obtained by spray drying was placed in a muffle furnace, calcined at 250°C for 3 hours, filtered and washed with deionized water for 3 times, and then transferred to a forced air drying oven and dried at 80°C for 6 hours to obtain a lithium iron phosphate / nitrogen-doped carbon / graphene composite material precursor.
[0032] The lithium iron phosphate / nitrogen-doped carbon / graphene composite material precursor was placed in a tubular furnace, heated to 600° C. at a rate of 3° C. / min in an argon atmosphere, and kept warm for 10 hours to obtain a lithium iron phosphate / nitrogen-doped carbon / graphene composite material.
[0033] The prepared lithium iron phosphate / nitrogen-doped carbon / graphene composite material was characterized by XRD and SEM. Figure 1 and Figure 2 shown.
[0034] From the XRD pattern ( Figure 1) can be seen that the sharp main characteristic diffraction peaks in the spectrum correspond well to the standard PDF card of LiFePO4 (JCPDS No.83-2092), indicating that the LiFePO4 in the composite material is an olivine structure with a space group of Pmnb. The characteristic peaks at 2θ=17.1°, 20.7°, 25.5°, 29.7° and 35.5° correspond to the (200), (101), (111), (211) and (311) crystal planes, respectively. In addition, the three characteristic diffraction peaks appearing at 2θ=15.2°, 22.3° and 43.7° indicate that the biomass material in the composite material is completely carbonized into nitrogen-doped carbon material and graphene oxide is reduced to graphene. The weaker and wider characteristic peak at 15.2° is attributed to the (001) peak of graphitized carbon nitride, indicating that N atoms are doped into graphitic carbon. The broad characteristic diffraction peak at 22.3° indicates that the obtained carbon material has a low degree of graphitization. Based on the above results, it is shown that the prepared composite material is composed of lithium iron phosphate and carbon, and the high-temperature pyrolysis process realizes the transformation of biomass materials into nitrogen-doped carbon materials and graphene oxide into graphene. No other impurity peaks were found in the spectrum, which can indicate that the prepared material has a high purity.
[0035] From the SEM images ( Figure 2 ) can be observed that there are a large number of mesh and flocculent substances on the surface and inside of the spherical particles. These are nitrogen-doped carbon generated after thermal decomposition of biomass and graphene obtained by reduction of graphene oxide. These carbon materials distributed on the surface and inside of the particles, on the one hand, form a good conductive network on the surface of LiFePO4 particles, which not only strengthens the contact between particles, but also improves the conductivity between particles, provides a good channel for the transmission of electrons during the charge / discharge process, and reduces polarization; on the other hand, the carbon layer coated on the surface of LiFePO4 particles can inhibit the growth of grains during crystal growth, reduce the grain size, shorten the lithium ion deintercalation path, and improve the diffusion coefficient of lithium ions. It can further improve the electrochemical lithium storage performance of the composite material.
[0036] Example 2 Preparation Example 2
[0037] Disperse 1 gram of chitosan powder in 250 mL of a mixed aqueous solution with a lithium hydroxide / urea mass ratio of 3:1, where the lithium hydroxide concentration is 1 mol / L, containing 12 grams of lithium hydroxide, 4 grams of urea, and the mass ratio of chitosan powder to lithium hydroxide is 1:12. Add 60 mL of 1.5 mg mL -1 The carbon nanotube aqueous solution was acidified and subjected to a low-temperature freezing-thawing cycle to obtain a uniform biomass / carbon nanotube mixed solution, and the number of repeated low-temperature freezing / thawing was 4 times.
[0038] A certain amount of 6 g of lithium iron phosphate powder was added to the mixed solution obtained above, and the mixture was thoroughly mixed to obtain a lithium iron phosphate / biomass / carbon nanotube mixed slurry; then spray drying was performed to obtain a lithium iron phosphate / biomass / carbon nanotube composite material powder; the operating parameters of the spray dryer were set as follows: inlet temperature 150°C, outlet temperature 110°C, atomizer operating pressure 100 kPa, and feed rate 70 mL / h.
[0039] The powder obtained by spray drying was placed in a muffle furnace, calcined at 200°C for 12 hours, filtered and washed three times with deionized water, and then transferred to a forced air drying oven and dried at 80°C for 6 hours to obtain a lithium iron phosphate / nitrogen-doped carbon / carbon nanotube composite material precursor.
[0040] The lithium iron phosphate / nitrogen-doped carbon / carbon nanotube composite material precursor was placed in a tubular furnace, heated to 800° C. at a rate of 2° C. / min in an argon atmosphere, and kept warm for 5 hours to obtain a lithium iron phosphate / nitrogen-doped carbon / carbon nanotube composite material.
[0041] Example 3 Preparation Example 3
[0042] Disperse 2 g of cellulose powder in 250 mL of a mixed aqueous solution with a sodium hydroxide / urea mass ratio of 1:1, where the sodium hydroxide concentration is 1 mol / L, containing 10 g of sodium hydroxide, 10 g of urea, and the mass ratio of cellulose powder to sodium hydroxide is 1:5. Add 50 mL of a 2 mg·mL -1 The graphene oxide solution is subjected to a low-temperature freezing-thawing cycle to obtain a uniform biomass / graphene oxide mixed solution, and the number of repeated low-temperature freezing / thawing cycles is 3.
[0043] A certain amount of 9 g of lithium iron phosphate powder was added to the mixed solution obtained above, and the mixture was thoroughly mixed to obtain a lithium iron phosphate / biomass / graphene oxide mixed slurry; then spray drying was performed to obtain a lithium iron phosphate / biomass / graphene oxide composite material powder; the operating parameters of the spray dryer were set as follows: inlet temperature 260°C, outlet temperature 130°C, atomizer working pressure 250 kPa, and feed rate 200 mL / h.
[0044] The powder obtained by spray drying was placed in a muffle furnace, calcined at 380°C for 1 hour, filtered and washed with deionized water for 3 times, and then transferred to a forced air drying oven and dried at 80°C for 6 hours to obtain a lithium iron phosphate / nitrogen-doped carbon / graphene composite material precursor.
[0045] The lithium iron phosphate / nitrogen-doped carbon / nano-carbon composite material precursor obtained in the above steps was placed in a tubular furnace, heated to 1000° C. at a rate of 3° C. / min in an argon gas atmosphere, and kept warm for 1 hour to obtain a lithium iron phosphate / nitrogen-doped carbon / graphene composite material.
[0046] Example 4 Electrochemical Effect Test
[0047] The lithium iron phosphate / nitrogen-doped carbon / graphene composite material prepared in Example 1 was used as an electrochemically active material, and the active material, the conductive agent (Super-P) and the binder (polyvinylidene fluoride, PVDF) were prepared into a positive electrode in a mass ratio of 8:1:1. The prepared lithium iron phosphate / nitrogen-doped carbon / graphene electrode was used as a working electrode, the metal lithium sheet was used as a counter electrode and an auxiliary electrode, and the electrolyte was prepared by mixing ethylene carbonate and dimethyl carbonate (EC / DMC) in a volume ratio of 1:1 to prepare 1 mol L -1 LiPF6 solution, Celgard 2400 microporous polypropylene membrane as lithium ion battery separator, assembled half-cell. -1 ) and 5C rate were used for constant current charge / discharge test. The results are as follows Figure 3 and Figure 4 As shown. Figure 3 and 4 It can be seen that the charge / discharge capacity of the lithium iron phosphate / nitrogen-doped carbon / graphene composite material prepared in Example 1 at 1C and 5C rates is 156.02 mAh g -1 and 154.75mAh g -1 , 127.02mAh g -1 and 126.77mAh g -1 The lithium iron phosphate / nitrogen-doped carbon / graphene composite material exhibits excellent rate capability and electrochemical reversibility.
Claims
1. A method for preparing a lithium iron phosphate / nitrogen-doped carbon / nanocarbon composite material, characterized in that The steps include: Step S1: dispersing biomass material powder in an aqueous solution of strong alkali and urea, adding a nanocarbon material solution, and obtaining a biomass / nanocarbon material mixed solution after a low-temperature freezing-thawing cycle, wherein the concentration of the strong alkali in the aqueous solution of strong alkali and urea is 0.2-3 mol / L, the mass ratio of the strong alkali to urea is 1-4:1, and the number of repeated low-temperature freezing / thawing is 3 or 4 times; the biomass material is chitin, and the nanocarbon material solution is an acidified carbon nanotube or graphene oxide aqueous solution; Step S2: adding lithium iron phosphate powder to the mixed solution, mixing to obtain a lithium iron phosphate / biomass / nano-carbon material mixed slurry, and then spray drying to obtain a lithium iron phosphate / biomass / nano-carbon composite material powder; Step S3: placing the composite material powder into a muffle furnace, calcining at low temperature, washing and drying, to obtain a lithium iron phosphate / nitrogen-doped carbon / nano-carbon composite material precursor, wherein the low temperature calcination temperature is 200 to 380° C., and the calcination time is 1 to 12 hours; Step S4: placing the precursor into a tubular furnace and calcining in an inert gas atmosphere at a sintering temperature of 600-1000° C. for a holding time of 1-10 h to obtain a lithium iron phosphate / nitrogen-doped carbon / nano-carbon composite material.
2. The preparation method according to claim 1, characterized in that: The strong base is one of sodium hydroxide, potassium hydroxide or lithium hydroxide, or a mixture of two or more of them in any proportion.
3. The preparation method according to claim 1, characterized in that: The concentration of the nanocarbon material solution is 0.1-5 mg·mL -1 The mass ratio of the biomass material to the strong base is 1:4-12.
4. The preparation method according to claim 1, characterized in that: The concentration of the strong base in the aqueous solution of the strong base and urea is 1-2 mol / L, and the mass ratio of the strong base to the urea is 1-3:1; the mass ratio of the biomass material to the strong base is 1:5-12; in the step S3, the temperature of the low-temperature calcination is 200-300°C.
5. The preparation method according to claim 1, characterized in that: In step S2, the spray drying parameters are set as follows: inlet temperature 150-260° C., outlet temperature 80-130° C., atomizer working pressure 100-250 kPa, and feed rate 60-200 mL / h.
6. The preparation method according to claim 1, characterized in that: In step S4, the inert atmosphere is high-purity nitrogen or argon, and the heating rate is 2-10°C / min.
7. The preparation method according to claim 1, characterized in that: In the step S2, the mass ratio of lithium iron phosphate to nano-carbon material is 60-120:
1.
8. The preparation method according to claim 7, characterized in that: In the step S2, the mass ratio of lithium iron phosphate to nano-carbon material is 60-100:
1.
9. A lithium iron phosphate / nitrogen-doped carbon / nanocarbon composite material, characterized in that It is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the composite material according to claim 9 as a positive electrode material for lithium ion batteries.
Citation Information
Patent Citations
Preparation method for low-resistivity lithium iron phosphate / carbon composite material
CN105742590A
Repairing and regenerating method of waste lithium iron phosphate battery positive electrode material and application
CN113782857A
Biomass carbon coated sodium ferric phosphate composite material as well as preparation method and application thereof
CN115275207A